BREAKING BARRIERS FROM CLASSROOM TO CAMPUS: ENHANCING HIGHER EDUCATION ACCESS FOR PWD STUDENTS WITH LEARNING DISABILITIES IN SELANGOR (Proceedings of International Conference on Special Education, 2025)
This study examines the systemic barriers faced by students with Specific Learning Disabilities (SLD) in accessing higher education in Selangor, Malaysia. Students with SLD, the transition to post-secondary education can be difficult, particularly for those who do not possess formal academic qualifications such as the Malaysian Certificate Education (Sijil Pelajaran Malaysia) (Sowell & Miller Scott, 2019). Their aspirations are limited by structural barriers, lack of institutional access and pathways into further study and employment. On the other hand, this study investigates the key obstacles that Person with Disabilities (PWD) especially focus on SLD students in Selangor experienced in accessibility, academic and institutional preparedness. It explores how far colleges and universities are prepared to admit and accommodate these students through such measures as alternative admissions policies and inclusionary practices. This is then followed up by a discussion on the extent to which the industry is prepared to welcome SLD graduates and an exploration of workplace inclusivity and perceptions of both employers and employment support systems. These issues are proposed to be addressed, among others, through the establishment and institutionalisation of alternative credentialing, bridging programme and skills-based educational pathways in higher education institutions in the state of Selangor. These programs are aimed at supporting PWD learners more effectively and enabling them to access higher education by following distinct pathways, thereby enhancing their employment outcomes. These findings aim to guide policymakers, educators, and industry leaders in transforming practices and policies.